IDENTIFIKASI JENIS ANGGUR LAUT (Caulerpa sp.) TELUK SEPANG KOTA BENGKULU - Ines Septiyaningrum; Maya Angraini Fajar Utami; Yar Johan (Jurnal Perikanan Unram, 2020)
This study aims to identify the type and analyze the density of the Caulerpa sp. at Sepang Bay Beach, Bengkulu City. This research was conducted in July-August 2020. The research method used a survey method. The data collected in this study are primary data and secondary data. The observed water quality, such as the temperature obtained at the time of the study, was 30-31oC, pH value was 7.7-7.8, brightness ranged from 0.5–0.68 meters. Three species of Caulerpa sp. were found in Teluk Sepang Beach, Bengkulu City with each relative density value, namely Caulerpa taxifolia (46.6 ind / m2), Caulerpa racemosa (52.1 ind / m2) and Caulerpa lentillifera (1.2 ind / m2)).